International Entrepreneurship at a Leading Brazilian Software Services Provider: The Case of CI&T - de Almeida Moraes, Sylvia T.; da Rocha, Angela (Internext, 2020)
Objective: This case aims at discussing to what extent a company from an emerging country, Brazil, can become a major player on the global stage of the software industry. Method: Teaching case, based on personal interviews with top executives and secondary data. Main results: CI&T is one of the most successful Brazilian IT companies in establishing a position in foreign markets. The case offers a detailed description of the internationalization process of the firm and discusses how the firm can develop its internationalization, facing the challenges and opportunities for further expansion. Relevance/originality – This teaching case offers a real situation of an IT company from Brazil that developed a successful international strategy. Theoretical / Methodological Contributions – The case contributes to foster the understanding of the three major liabilities of companies from emerging countries – liabilities of foreignness, liabilities of outsidership and liabilities of smallness. Social / management contributions – The case can be used in International Business courses to improve managerial skills of students and executives.